Sobre psicologia e ideologia na obra de L. S. Vigotski - Silva, Rafael Iglesias Menezes da (2015)
The dissertation that follows aims to discuss the problem of the ideology as from the classic conceptions of Marx and Engels and of its interlacement to selected essays about this theme written by the Belarusian psychologist L. S. Vigotski, through an analysis that includes the itinerary of the concept of ideology, the exposition of the fundamental thesis about it in the classic essays of Marx and Engels, and of its appearance in Vigotski's literature, suggesting a link amongst these authors, but highlighting the particularity of the latter when it comes to the application of the concept of ideology in the Psychological Science and for the Cultural-historical Psychology. The hypothesis is that the formulations of Vigotskymatch to the inherent tension in Marxist heritage of ideology between two fundamental lines, a critical-negative, epistemological, and the other one related to the functions and systems that belongs to the consciousness of the social life. Is therefore justified the survey of the literature related to the word "ideology", as well as its historical contextualization and the theses that define it, aiming to answer issues, such as: a) Is the diagnose of Vigotsky about the shadow of the ideology over the Psychological Science still current if we think of the practice of this Science, of how it in fact effectives itself? b) Do the conceptual nuances of ideology permit to recognize a direct influence of Marx on what this author shares about the classic definition of ideology? c) Does the concept of ideology found on Vigotsky's literature modify, is it continuous, does it expand? Does it remain the same? Is that what we can take from it for the comprehension of an inventive Cultural-historical of the psyche similar to the already established approaches of Social Psychology and School Psychology on the matter of ideology? In order to answer these issues, this dissertation was structured in three chapters: The first one aims to expose the problem of ideology in its origin and contrast the reason Marx followed to dedicate a whole work to this theme, as well as its implications due to a Marxist view of men about the consciousness and the alienation. Moreover, point the appearance of ?ideology? in essays belonging to the maturity of Marx that lead to amplified comprehensions related to The German Ideology. The second chapter exposes the result of the survey about the highlighted word in the selected essays of L. S. Vigotsky, making explicit the theses that involve its use in these essays and searching for demonstrate a variation amid the essays of 1924- 1927. At least the third chapter discusses the works of Vigotski between the years of 1929 ? 1931 that implies the adhesion of Vigotski definition of ideology that not reduced to the sense of negativity or false counsciouness and get that social conceptual systems to explain that conceptual thoughts and the superation of spontaneous our dominant ideology.